Mapping Religious Harmony in the Special Capital Region Jakarta using K-Means Algorithm - Istiawan, Deden; Sulistijanti, Wellie; Santoso, Arif Gunawan; Ustyannie, Windyaning (Universitas Muhammadiyah Semarang Press, 2023)
D.K.I Jakarta is often called the window of Indonesia. As one of the largest cities in Indonesia, D.K.I Jakarta has various kinds of complex social problems. This research tries to identify and explore conditions of religious harmony in DKI Jakarta. In previous studies of religious harmony, the use of the index in assessing religious harmony could only describe the condition of religious harmony in general without indicating which factor was in measuring the level of religious harmony. This Research uses a clustering approach to analyse religious harmony in DKI Jakarta. The study found that cluster 0 has major problems that affect religious harmony compared to other clusters. Therefore, local government policies related to increasing religious harmony can be focused more on cluster 0, especially on variables that are shown to be low, namely empathy, non-violence, national commitment, and adaptability to local culture.